Modified Intervastus Approach to the Knee - Sartawi, Muthana; Kohlman, James; Valle, Craig Della (The Journal of Knee Surgery, 2018)
The modified intervastus approach to the anterior knee is an approach that may be used in the majority of patients undergoing total knee arthroplasty. This article presents the first description of this approach. The advantages of this approach include its extensile nature, similar to a medial parapatellar approach, and preservation of the extensor mechanism and the vastus medialis, leading to a more rapid return to active knee extension than is traditionally observed. The approach is also simple to perform, easy to close, and is compatible with more extensile approaches such as a quadriceps snip if required in revision scenarios.
Keywords: muscle sparing; quadriceps sparing; minimally invasive; total knee arthroplasty; total knee revision